REGULATION OF LOSS-INDUCING CRYPTO ASSET INVESTMENTS: CHALLENGES IN REGULATION, PROTECTION AND SUPERVISION - Anggasta, Giovani; Kusumadara, Afifah; Nur Widhiyanti, Hanif (IJBLE Scientific Publications Community Inc., 2023)
Cryptocurrency has become evidence of the rapid growth of the digital economy. This phenomenon has left countries worldwide in a dilemma regarding the legal status of cryptocurrencies. Specifically in Indonesia, cryptocurrency is regulated in a limited manner, creating a gap in legal protection for investors. This research employs a normative research method with a legislative and conceptual approach. The findings of this research indicate that Indonesia tends to position cryptocurrencies in a